Serendipita indica-dominated synthetic microbial consortia enhanced tartary buckwheat growth and improved its tolerance to drought stress - Zhong, Shanpu; Wang, Wenjing; Tang, Wuyao; Zhou, Xingmei; Bu, Tongliang; Tang, Zizhong; Li, Qingfeng (Frontiers in Microbiology, 2025)
The cultivation of tartary buckwheat serves dual roles, offering health benefits and nutritional advantages. Nonetheless, its cultivation is challenged by issues such as soil degradation and climatic drought. Plant growth-promoting (PGP) microorganisms hold promise for addressing these challenges. In this study, we investigated the effects of Serendipita indica inoculation on the root-associated microbial communities of tartary buckwheat. Additionally, we used S. indica to construct synthetic microbial consortia, and their role in promoting the growth and enhancing the drought resistance of tartary buckwheat was evaluated. This study found that the colonization of S. indica in tartary buckwheat promoted the enrichment of beneficial microorganisms such as Actinobacteriota, Sphingomonas, and Mortierella, while reducing the relative abundance of pathogenic genera including Cladosporium, Alternaria, and Acremonium. In addition, the inoculation of the microbial consortia significantly promoted the photosynthesis and biomass accumulation of tartary buckwheat, while also improving soil structure and fertility. Under drought conditions, introducing microbial groups markedly boosted root development, lowered the density of stomata and rate of transpiration in tartary buckwheat leaves, and decreased H2O2 and Malondialdehyde (MDA) levels, thus greatly enhancing tartary buckwheat’s resistance to drought. In conclusion, our findings demonstrated that the microbial consortia constructed with S. indica can significantly promote the growth of tartary buckwheat and enhance its drought resistance. However, the specific molecular mechanisms underlying these effects require further investigation in future studies. These findings will provide important theoretical support for the development of novel microbial fertilizers.